Kemampuan Representasi Matematis Ditinjau dari Perbedaan Gender Siswa Kelas IV SD pada Materi Pecahan Campuran - Lutfiah, Novi Novianti Sri; Irawati, Riana; Maulana, Maulana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the importance of mathematical representation ability in mixed fraction material. This study aims to describe the mathematical representation ability of fourth grade students in mixed fraction material based on gender. The research used quantitative method. The sample in this study were fourth grade students with a total of 34 students consisting of 16 male students and 18 female students. Selection of research subjects based on purposive sampling. Data were obtained through tests conducted twice, namely pretest then given treatment (treatment) and posttest with validated test instruments to see students' mathematical representation skills which were then processed and analyzed to draw conclusions and teacher questionnaires to see teacher perceptions about this research. The results showed that the average value of students' mathematical representation ability in visual representation reached 65.2%, representation of mathematical equations or expressions reached 43.5% and representation of words or written text reached 41.2%. Based on gender, male students reached an average of 0.61 and female students reached 0.44. The results of this study indicate that the mathematical representation ability of mixed fractions of male students is faster to accept the material because male students pay more attention to the material when learning so that they understand more quickly while female students play more.